Elucidation of artefacts in proton transfer reaction time‐of‐flight mass spectrometers. (11th December 2019) - Salazar Gómez, Jorge Iván; Klucken, Christian; Sojka, Martha; Masliuk, Liudmyla; Lunkenbein, Thomas; Schlögl, Robert; Ruland, Holger
Abstract: We present an effective procedure to differentiate instrumental artefacts, such as parasitic ions, memory effects, and real trace impurities contained in inert gases. Three different proton transfer reaction mass spectrometers were used in order to identify instrument‐specific parasitic ions. The methodology reveals new nitrogen‐ and metal‐containing ions that up to date have not been reported. The parasitic ion signal was dominated by [N2 ]H + and [NH3 ]H + rather than by the common ions NO + and O2 + . Under dry conditions in a proton transfer reaction quadrupole interface time‐of‐flight mass spectrometer (PTR‐QiTOF), the ion abundances of [N2 ]H + were elevated compared with the signals in the presence of humidity. In contrast, the [NH3 ]H + ion did not show a clear humidity dependency. On the other hand, two PTR‐TOF1000 instruments showed no significant contribution of the [N2 ]H + ion, which supports the idea of [N2 ]H + formation in the quadrupole interface of the PTR‐QiTOF. Many new nitrogen‐containing ions were identified, and three different reaction sequences showing a similar reaction mechanism were established. Additionally, several metal‐containing ions, their oxides, and hydroxides were formed in the three PTR instruments. However, their relative ion abundancies were below 0.03% in all cases. Within the series of metal‐containing ions, the highest contribution under dry conditions was assigned to the [Fe(OH)2 ]H + ion. Only in one PTR‐TOF1000 the Fe + ion appeared as dominant species compared with the [Fe(OH)2 ]H + ion. The present analysis and the resulting database can be used as a tool for the elucidation of artefacts in mass spectra and, especially in cases, where dilution with inert gases play a significant role, preventing misinterpretations.